The Interface of Cancer, Their Microenvironment and Nanotechnology - Roque, Natalia (2022)
Cancer is one of the deadliest diseases with a cure far from being found. Despite the extraordinary advances in the therapy approaches, only a few patients respond to treatments. The tumor microenvironment (TME) plays a crucial role in cancer progression by contributing to the chemoresistance. Thus, emerging efforts are being made in nanotechnology research focusing on nanoparticles' potential role and their application in immune system modulation. Moreover, the omics have contributed to bioengineering and nanotechnology development by elucidating the mechanisms of cancer and specific biomarkers that could be used as new therapeutic targets. Furthermore, the non-coding microRNA as a target for cancer treatment and creation of organoids for the study of new treatments helped for the new therapeutics' era called personalized medicine. Here we will discuss the role played by TME in tumor initiation and progression we will describe the recent nanotechnology applied to cancer treatment. Specifically, we will describe the potential role of nanoparticles (NPs) and their application in immune system modulation, ultimately leading to circumventing tumor cell proliferation.